Opium Consumption and its Indirect Effect on the Fertility of Women In Desert Villages of Rajasthan - Lakshminarayana, j; Misra, K N; Singh, Madhu B; Kalundha, R K (Annals of Arid Zone, 2016)
The study was carried out in 1998 in two rural desert districts namely, Barmer and Bikanpr of Rajasthan where the consumption of opium or doda is very much prevalent due to social and cultural customs in the area. The median age of the addicts was 41.1 years. The mean age of the opium/ doda addiction, the mean age at marriage, mean age at effective marriage and duration of consumption of opium have been found out. The indirect effect of opium and doda addiction by men and the changes in the fertility of their spouse in terms of parity has been estimated with the help of a discrete probability model. The probability model has been estimated with closed birth interval technique. The nature of variation of addiction of opium/doda by the husbands and its effect on the wives fertility with respect to age, duration of consumption and parity was estimated. Key words: Opium addiction by men, indirect effect, fertility, women, desert, Rajasthan.